2018
DOI: 10.15403/jgld.2014.1121.271.eus
|View full text |Cite
|
Sign up to set email alerts
|

EUS-guided Radiofrequency Ablation (EUS-RFA) of Solid Pancreatic Neoplasm Using an 18-gauge Needle Electrode: Feasibility, Safety, and Technical Success

Abstract: Background & Aims: Endoscopic ultrasound-guided radiofrequency ablation (EUS-RFA) is a promising technique for the treatment of pancreatic neoplasm. We evaluated the feasibility, safety, and technical success of pancreatic EUS-RFA performed in a single center.Methods: 9 consecutive patients (8 with pancreatic adenocarcinoma and 1 with renal cancer metastasis) were referred for EUS-RFA between November 2016 and July 2017. EUS-RFA was performed using 18-gauge internally cooled electrode with a 5 or 10 mm exp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
87
0
1

Year Published

2020
2020
2022
2022

Publication Types

Select...
3
2
1

Relationship

0
6

Authors

Journals

citations
Cited by 97 publications
(89 citation statements)
references
References 20 publications
1
87
0
1
Order By: Relevance
“…Previous experiments of 1 to 8 patients have been published showing the feasibility of EUS-RFA in this setting (Table 1). 11,[14][15][16][17][18][19][20][21][22][23] One recent prospective study 11 including 14 PNENs (G1, <2 cm) demonstrated a 6-months success rate of 71%, whereas 85.7% of tumors completely disappeared at 12 months, possibly due to the late response related to RFA related immunomodulation. Two RFA related adverse events of acute necrotic pancreatitis and pancreatic duct stricture developed.…”
Section: Clinical Applications Pancreatic Neuroendocrine Neoplasmmentioning
confidence: 99%
See 4 more Smart Citations
“…Previous experiments of 1 to 8 patients have been published showing the feasibility of EUS-RFA in this setting (Table 1). 11,[14][15][16][17][18][19][20][21][22][23] One recent prospective study 11 including 14 PNENs (G1, <2 cm) demonstrated a 6-months success rate of 71%, whereas 85.7% of tumors completely disappeared at 12 months, possibly due to the late response related to RFA related immunomodulation. Two RFA related adverse events of acute necrotic pancreatitis and pancreatic duct stricture developed.…”
Section: Clinical Applications Pancreatic Neuroendocrine Neoplasmmentioning
confidence: 99%
“…Available experiments of EUS-RFA of PDAC include a few small cohorts and focus mainly on technical feasibility and safety (Table 1). 11,[14][15][16][17][18][19][20][21][22][23] From these researches, EUS-RFA is technically feasible and has no major procedure-related adverse events such as mortality. Most RFA related adverse events were minor, such as self-limiting postprocedural abdominal pain.…”
Section: Pancreatic Ductal Adenocarcinomamentioning
confidence: 99%
See 3 more Smart Citations